Keragaman Morfologi Genetik Dan Kualitas Buah Manggis (Garcinia Mangostana L.) di Provinsi Aceh - Qinanti Lubis, Uchti Nuzul; Akmal, Ajmir; Fridayati, Diah (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2023)
Mangosteen (Garcinia mangostana L.) is an exotic tropical fruit that has many benefits such as refreshing and stimulant. This plant is believed to be native to Sumatra. Despite its importance to the local economy, however, the presence of mangosteen in Aceh Province is rarely reported. The aim of this research is to access mangosteen in Aceh regarding distribution, production, genetic variability and land suitability for mangosteen production. Research was conducted in three main production centers, namely, North Aceh, East Aceh and Pidie Jaya District from August-November 2016. Mangosteen characters, cultivation methods and quality were evaluated from field visits and interviews with farmers and merchandisers. The research results show that mangosteen is widely distributed in Aceh. Most of the trees in wild populations with ages ranging from 40 to 70 years, are cultivated in forests known as 'mangosteen forests' as well as in home gardens. Mangosteens show great variation in tree morphology, leaves, and fruit. Flowering times vary between regions. The hydrological conditions in Aceh and agroecological suitability for producing mangosteen are very good